Effect of hot versus cold climates on power output, muscle activation, and perceived fatigue during a dynamic 100-km cycling trial - Abbiss, C. R.; Burnett, A.; Nosaka, K.; Green, J. P.; Foster, J. K.; Laursen, P. B. (Journal of Sports Sciences, 2010)
The purpose of this study was to examine the influence of environmental temperature on power output, muscle activation, body temperature, and perceived physical strain during a dynamic self-paced 100-km cycling trial. Nine endurance-trained male cyclists (mean ± s: age 31 ± 6 years; [VO2max 62.1 ± 8.5 ml/kg·min) completed two 100-km experimental trials, interspersed with five 1-km and four 4-km high-intensity epochs, in hot (34°C) and cold (10°C) environments. Measurements consisted of power output, rectal and skin temperature, muscle activation of vastus lateralis, biceps femoris and soleus, ratings of perceived exertion, thermal sensation and pain intensity in the quadriceps. Power output and muscle activation of the biceps femoris and soleus were lower in the hot trial (22 km; P < 0.05) prior to significant (P < 0.05) differences in rectal temperature [38.8°C (cold) vs. 39.1°C (hot)] at 42 km. Muscle activation of the vastus lateralis, biceps femoris, and soleus was significantly (P < 0.001) correlated with power output and thermal sensation (r > 0.68) but not with perceived pain or exertion. Thus, a hyperthermic-induced anticipatory reduction of muscle activation may have occurred during the hot exercise trials only. Fatigue and pacing during prolonged dynamic exercise in the cold appears to be influenced by factors dissociated from hyperthermic-induced stress.